The Venetian Painters of the Renaissance : Third Edition - Berenson, Bernard, 1865-1959 (Salt Lake City, UT : Project Gutenberg, 2007)
"The Venetian Painters of the Renaissance" by Bernard Berenson is a historical account written in the late 19th century. The book explores the significance and unique characteristics of Venetian painting within the broader context of the Renaissance art movement. It discusses various artists and their contributions to the evolution of this art form, emphasizing how Venetian painting captured the spirit of the Renaissance in an unmatched way. The opening portion introduces the foundation of the author's exploration, highlighting his belief that Venetian painting embodies the quintessential expression of the Italian Renaissance. Berenson argues that while the Renaissance had complex historical implications, it also represented a youthful exploration of human experience and emotion. He emphasizes how Venetian painters, such as Giovanni Bellini and Giorgione, exhibited a mastery over color and composition, which engaged not only the senses but also provided profound emotional experiences. This initial discussion sets the stage for a deeper analysis of the prominent Venetian artists and their works, inviting readers to appreciate the elevating and transformative power of art during this vibrant period. (This is an automatically generated summary.)
Release date is 2007-07-23
E-text prepared by Juliet Sutherland, Chuck Greif, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Art, Renaissance; Painters -- Italy -- Venice